2016
DOI: 10.3390/nu8100593
|View full text |Cite
|
Sign up to set email alerts
|

Using Two Different Approaches to Assess Dietary Patterns: Hypothesis-Driven and Data-Driven Analysis

Abstract: The use of dietary patterns to assess dietary intake has become increasingly common in nutritional epidemiology studies due to the complexity and multidimensionality of the diet. Currently, two main approaches have been widely used to assess dietary patterns: data-driven and hypothesis-driven analysis. Since the methods explore different angles of dietary intake, using both approaches simultaneously might yield complementary and useful information; thus, we aimed to use both approaches to gain knowledge of ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 36 publications
(72 reference statements)
0
44
2
2
Order By: Relevance
“…In contrast to this study, Previdelli et al [10] verified high scores for oils, probably because they considered frying oils, unlike the present research. It is noteworthy that the oil component aims to capture good sources of the food.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to this study, Previdelli et al [10] verified high scores for oils, probably because they considered frying oils, unlike the present research. It is noteworthy that the oil component aims to capture good sources of the food.…”
Section: Discussioncontrasting
confidence: 99%
“…There is a shortage of studies on diet quality of Brazilian adolescents by BHEI-R. Among these, Wendap et al [43] obtained a mean BHEI-R score higher than that of this research (75.1 points), while Previdelli et al [10] found a lower mean (47.1 points). In a population-based study, the mean BHEI-R of adolescents was closer to that of this research (52.4 points) [46].…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Two methods of dietary assessment were used in this study; a Food Frequency Questionnaire (FFQ) and 24-h recall. More than one method of assessing dietary intake is recommended as one method is susceptible to biases (Previdelli et al, 2016).…”
Section: Dietary Assessmentmentioning
confidence: 99%